An Approach to Reduce Tuning Sensitivity in the PIC-Based Optoelectronic Oscillator by Controlling the Phase Shift in Its Feedback Loop - Vladislav Ivanov; Ivan Stepanov; Grigory Voronkov; Ruslan Kutluyarov; Elizaveta Grakhova (Micromachines)
Radio photonic technologies have emerged as a promising solution for addressing microwave frequency synthesis challenges in current and future communication and sensing systems. One particularly effective approach is the optoelectronic oscillator (OEO), a simple and cost-effective electro-optical system. The OEO can generate microwave signals with low phase noise and high oscillation frequencies, often outperforming traditional electrical methods. However, a notable disadvantage of the OEO compared to conventional signal generation methods is its significant frequency tuning step. This paper presents a novel approach for continuously controlling the output frequency of an optoelectronic oscillator (OEO) based on integrated photonics. This is achieved by tuning an integrated optical delay line within a feedback loop. The analytical model developed in this study calculates the OEO’s output frequency while accounting for nonlinear errors, enabling the consideration of various control schemes. Specifically, this study examines delay lines based on the Mach–Zehnder interferometer and microring resonators, which can be controlled by either the thermo-optic or electro-optic effect. To evaluate the model, we conducted numerical simulations using Ansys Lumerical software. The OEO that utilized an MRR-based electro-optical delay line demonstrated a tuning sensitivity of 174.5 MHz/V. The calculated frequency tuning sensitivity was as low as 6.98 kHz when utilizing the precision digital-to-analog converter with a minimum output voltage step of 40 μV. The proposed approach to controlling the frequency of the OEO can be implemented using discrete optical components; however, this approach restricts the minimum frequency tuning sensitivity. It provides an additional degree of freedom for frequency tuning within the OEO’s operating range, which is ultimately limited by the amplitude-frequency characteristic of the notch filter. Thus, the proposed approach opens up new opportunities for increasing the accuracy and flexibility in generating microwave signals, which can be significant for various communications and radio engineering applications.